Heritability and genetic advance in vegetable pea (Pisum sativum L.) - Kumari, Nitu; Srivastava, J.P.; Singh, S.K.; Singh, I.P. (Annals of Agricultural Research, 2014)
Ten pea genotypes crossed in a diallel mating design excluding reciprocals were evaluated with their 45 F1’s along with parents in a randomized block design in three replications at the Department of Vegetable Science, C.S. Azad University of Agriculture and Technology, Kalyanpur, Kanpur, during winter season 2007-08. The heritability and genetic advance were studied for all the traits under study. The estimates of heritability varied from 9.12 % (pod width) to 63.25% (number of first fruiting node). The heritability estimates were moderate for pod length and shelling percentage; low for pod width and ash content. For remaining characters, estimates of heritability were high. Genetic advance was highest for number of pods per plant while four characters viz. plant number of pods per plant, plant height, length to first fruiting node and days to flowering showed high genetic advance (more than 30%), while pod width showed lowest genetic advance. Other traits showed moderate genetic advance. The consequences of heritability coupled with genetic advance showed that four characters viz. number of pods per plant, plant height, length to first fruiting node and days to flowering had high heritability as well as high genetic gain, thus, these characters may be improved through selection method.